PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA "PERCETAKAN KUSUMA" SITUBONDO - Fattah, Rozikin Miftahul; Karnadi, Karnadi; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Developments in the printing industry have experienced good growth in the current digital era, banners or billboards are plastered on almost every street and sales are increasing which involve printing as a medium, especially in printing books, newspapers and comics which are often read by the public. The aim of this research is to analyze and test the influence of price, product quality and service quality on loyalty through consumer satisfaction as an intervening variable at Kusuma Printing in Situbondo. The target respondents for this research are Kusuma Printing consumers using a simple random sampling method. The data analysis and hypotheses used the Structural Equation Model–Partial Leas Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that price has a positive but not significant effect on consumer satisfaction. The product quality has a significant positive effect on consumer satisfaction. The service quality has a significant positive effect on consumer satisfaction. The price has a negative but not significant effect on Loyalty. The product quality has a positive but not significant effect on Loyalty. The service quality has a negative but not significant effect on loyalty. The consumer satisfaction has a significant positive effect on Loyalty. The price has a positive but not significant effect on consumer satisfaction. The product quality has a positive but not significant effect on loyalty through consumer satisfaction. The service quality has a significant positive effect on loyalty through consumer satisfaction.